2022
DOI: 10.1007/s10072-021-05802-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical heterogeneity in patients with myoclonus associated to COVID-19

Abstract: Objective This study aims to report the clinical heterogeneity of myoclonus in 6 patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods Patient data were obtained from medical records from the University Hospital Dr. Josep Trueta, Girona, Spain. Results Six patients (5 men and 1 woman, aged 60–76 years) presented with different myoclonus phenotypes. All of them had a medical history of hypertension and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The production of recombinant monoclonal antibodies from the CSF (plasmablasts) of such patients and pathogenicity assessment in animal models could provide more solid information regarding their functionality. Thirty-one cases of myoclonus and ataxia associated with COVID-19 were reported in a recent review article [ 5 ], and eleven more cases were reported in five case reports and case series afterwards [ 23 , 24 , 25 , 26 , 27 , 28 ]. In one of these cases, anti-GFAP-antibodies were identified [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of recombinant monoclonal antibodies from the CSF (plasmablasts) of such patients and pathogenicity assessment in animal models could provide more solid information regarding their functionality. Thirty-one cases of myoclonus and ataxia associated with COVID-19 were reported in a recent review article [ 5 ], and eleven more cases were reported in five case reports and case series afterwards [ 23 , 24 , 25 , 26 , 27 , 28 ]. In one of these cases, anti-GFAP-antibodies were identified [ 29 ].…”
Section: Discussionmentioning
confidence: 99%